A Reflection on Three Web-Based Teaching Critical Thinking: Toward A Compromise Approach - Shabani VARAKI Bakhtiar (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
Many literature reviews have shown that Webbased Instruction (WBI) is an effective learning tool for general education courses which require lower order thinking skills.There is not sufficient evidence to support the effectiveness of WBI in teaching courses which require higher order thinking skills, critical thinking. Therefore, the main question is whether Web-based Instruction can successfully promote critical thinking. The purpose of this paper is to find an answer to this question. It also will identify the teaching strategies and instructional designs which will successfully promote critical thinking in an electronic learning environment. Some preliminary result of this review could be articulated as follow: Critical thinking is significantly anchored within curricula and related teaching goal. It is highly correlated with students' achievements. According to Dick’s taxonomy critical thinking consists of identifying the arguments, considering external influences on the involved elements, applying scientific analytical reasoning, outlining chain of logical orders, and make conclusion. WBI can be an effective medium of instruction for promoting critical thinking if it is delivered on an instructional design specially developed for WBI